Predicting Intention to Buy Green Electric Vehicles Using an Extended Theory of Planned Behavior Approach - Imaningsih, Erna Sofriana; Ramli, Yanto; Marlapa, Eri; Wardhani, Nia Kusuma; Utama, Andyan Pradipta; Shah, Khairul Anuar Mohammad; Absamatov, Asqar (International Journal of Energy Economics and Policy, 2026)
The study investigates how behavioral values, environmental attitudes, subjective norms, environmental social influence, and environmental concern impact the intention of individuals to act pro-environmentally in enhancing the explanatory potential of the existing behavioral theories. The research employed Smart-PLS to determine the measurement and structural models using data obtained on 378 respondents. The findings supported the reliability and validity of all constructs and indicated that behavioral values serve as the most relevant cause of pro-environmental intentions. The behavioral values provided additional support on the role of environment in affecting intention as well as having an indirect impact on intention via environmental attitudes, concern, social influence and subjective norms and therefore the mediating processes are important. The results can be aligned with the Theory of Planned Behavior, Value-Belief-Norm framework, and Construal Level Theory, which state that values play a central role and psychological and social processes reinforce behavior. The research makes contributions to literature through the inclusion of personal and environmental variables into a cohesive approach of explaining sustainable behavioral intentions. In practice, the findings indicate that policymakers, teachers, and institutions ought to establish interventions which can promote environmental values but at the same time promote supportive attitudes, enhance concern and take advantage of social norms and peer pressure. These multidimensional approaches are likely to work more in encouraging pro-environmental behavior in the long-term.